2017
DOI: 10.1002/cmdc.201700287
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Radiotheranostic Agent for Dual Targeting of Breast Cancer Cells

Abstract: A straightforward synthetic route for a new multifunctional 1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetraacetic acid (DOTA) derivative is described. To demonstrate the versatility of this pro‐chelator for the preparation of radiolabeled hybrid compounds containing two different biological targeting moieties, an antitumor agent (e.g., a DNA‐intercalating agent) and an estrogen receptor (ER) ligand (e.g., LXXLL‐based peptide) were regiospecifically conjugated to the DOTA derivative. The bifunctional probe was ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…An early experiment was conducted by DeSombre et al (1992) , who showed that 123 I-labeled estrogen analogs result in a significant reduction in clonogenic survival of ER expressing cells. DeSombre and others subsequently evaluated various radiolabeled agents for the treatment of cancer, including 123 I- and 111 In-labeled analogs of estrogen and diethylstilboestrol, a non-steroid ER agonist ( DeSombre et al, 2000 ; Yasui et al, 2001 ; Fischer et al, 2008 ; Vultos et al, 2017 ). Kortylewicz et al (2012) developed an interesting hybrid molecule that exploits dual AR targeting and S-phase specific cell kill by linking 5α-dihydrotestosterone with 5-radioiodo-2′-deoxyuridine.…”
Section: Subcellular Targets For Radionuclide Therapymentioning
confidence: 99%
“…An early experiment was conducted by DeSombre et al (1992) , who showed that 123 I-labeled estrogen analogs result in a significant reduction in clonogenic survival of ER expressing cells. DeSombre and others subsequently evaluated various radiolabeled agents for the treatment of cancer, including 123 I- and 111 In-labeled analogs of estrogen and diethylstilboestrol, a non-steroid ER agonist ( DeSombre et al, 2000 ; Yasui et al, 2001 ; Fischer et al, 2008 ; Vultos et al, 2017 ). Kortylewicz et al (2012) developed an interesting hybrid molecule that exploits dual AR targeting and S-phase specific cell kill by linking 5α-dihydrotestosterone with 5-radioiodo-2′-deoxyuridine.…”
Section: Subcellular Targets For Radionuclide Therapymentioning
confidence: 99%
“…Compound 1, ethyl 4-((2-(tert-butoxycarbonylamino)ethyl) (2-(4-(2-(2,5-dioxopyrrolidinyloxy)-2-oxoethyl)-3,5-dimethylpyrazol)ethyl)amino) butanoate, was prepared as described in the literature [63]. Compound 2, 3,6-bis(dimethylamino)-10-(3-(1,3-dioxoisoindolin-2-yl)-propyl)acridinium iodide (2), was prepared according to the published methods [64]. The starting material fac-[Re(H 2 O) 3 (CO) 3 ]Br was synthesized according to the literature [65].…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, unlike G4-binders, several research groups have studied radiolabeled classical DNA intercalators aiming to deliver Auger electrons to short (sub)nanomolar distances to DNA and induce lethal DNA damage [76,[165][166][167][168][169][170][171]. In particular, these studies included complexes with Auger-electron emitting radiometals, such as 99m Tc and 111 In.…”
Section: Dna-targeted Radiocomplexesmentioning
confidence: 99%